Implementasi Pembelajaran Kolaboratif dalam Meningkatkan Empati dan Kerja Sama Antar Siswa di Kelas Inklusif SD - Vina Bella Pratiwi; Ibnu Muthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to describe the implementation of collaborative learning in enhancing empathy and cooperation in inclusive elementary school classrooms. Through a literature review, the researcher analyzed various sources related to collaborative strategies such as think-pair-share, jigsaw, and project-based learning. The findings indicate that collaborative learning effectively promotes positive interactions between regular students and students with special needs. It facilitates mutual understanding, respect for differences, and joint task completion. Strategies include heterogeneous group discussions, active teacher facilitation, and group reflections to strengthen empathy. Supporting factors include inclusive teacher attitudes and school support, while major obstacles involve time constraints, varying student abilities, and limited teacher training. In conclusion, collaborative learning shows strong potential in fostering inclusive, equitable, and humanistic classroom environments.